Lipid ratios as a predictive marker of Subclinical Atherosclerosis inflammation among Type 1 Diabetic patients with Thyroid Dysfunction - HAMRI, Walid Hassene; DIAF, Mustapha; HARIR, Noria; HADJ HABIB, Mohamed (Journal of Drug Delivery and Therapeutics, 2020)
Background and Objectives: Epidemiological inquiries on the subclinical atherosclerotic disease in type 1 diabetes associated with autoimmune thyroid disease are scarce. Our aim was to evaluate the risk of developing atherosclerosis via lipid ratios by comparing two groups of patients according to their TSH (Thyroid-stimulating hormone) status.Methods: A retrospective study including 190 patients (13-74 years) with confirmed type 1 diabetes divided into the following groups (patients with serum TSH < 2.5 μIU/mL vs. patients with serum TSH ≥ 2.5 μIU/mL). Autoimmune thyroid disease was classified according to clinical, biological, and follow up data.Results: Our study showed a slight predominance of females (50.50%), with an average age of 29.25±11.39 years. The prevalence of hypothyroidism was 14.7%, hyperthyroidism 6.3%, and anti-TPO 16.31%. Significant differences were observed between lipid profiles such as HDL and TG (p= 0.008; p=0.04, respectively). The results showed that the 3rd (OR= 2.28 [0.72-7.20]; p=0.15) and the fourth quartiles (OR= 1.9 [0.61-5.83]; p=0.26) of TC/HDL ratio were higher in patients with serum TSH ≥ 2.5 μIU/mL group. Similarly, we noticed higher concordant values on the last quartile (4th) of LDL/HDL ratio with p values of 0.06 as well as the two quartiles (2ndand 4th) of TG/HDL ratio with p values of 0.03 and 0.04, respectively. In both groups, lipid ratios were slightly higher in males compared to females’ patients.Conclusion: The risk of atherosclerosis was higher in patients with elevated TSH concentrations. Therefore, early detection of thyroid dysfunction and associated dyslipidemia is essential for effective prevention of premature cardiovascular morbidity and mortality.Keywords: Subclinical atherosclerotic disease, autoimmune thyroid disease, TSH, type 1 diabetes